2013
DOI: 10.5897/ajb12.2023
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of microcystin-producing microcystis in freshwater bodies in the Southern Mozambique using quantitative real time polymerase chain reaction

Abstract: In the last decades, large number of reported cases of illnesses in Mozambique is related to drinking water. However, only a limited number of studies have focused on aquatic pollution in this country. Cyanobacterial blooms dominated by Microcystis sp are regularly identified in freshwater bodies in Mozambique. Microcystis is known to proliferate in freshwater bodies and produce microcystins which have adverse effects on animals and humans. The aim of this study was to quantify microcystinproducing Microcystis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…These data indicate that many people of Mozambique consume food and water unsafely. Few studies (Figure 1) were done by Pedro et al [117][118][119] and Bojcevska and Jergil [120] in Pequenos Libombos dam, Nhambavale lake, Chòkwé irrigation channels and Chidenguele sites in the South of Mozambique during 2003Mozambique during , 2008Mozambique during , and 2009 and their studies indicated the occurrence of MC-LR, -YR, and -RR produced by Microcystis sp. (M. novacekii, botrys and other) and Cylindrospermopsis raciborskii [117][118][119][120] (Table 4).…”
Section: Microcystin In Mozambican Drinking Watermentioning
confidence: 99%
See 3 more Smart Citations
“…These data indicate that many people of Mozambique consume food and water unsafely. Few studies (Figure 1) were done by Pedro et al [117][118][119] and Bojcevska and Jergil [120] in Pequenos Libombos dam, Nhambavale lake, Chòkwé irrigation channels and Chidenguele sites in the South of Mozambique during 2003Mozambique during , 2008Mozambique during , and 2009 and their studies indicated the occurrence of MC-LR, -YR, and -RR produced by Microcystis sp. (M. novacekii, botrys and other) and Cylindrospermopsis raciborskii [117][118][119][120] (Table 4).…”
Section: Microcystin In Mozambican Drinking Watermentioning
confidence: 99%
“…Few studies (Figure 1) were done by Pedro et al [117][118][119] and Bojcevska and Jergil [120] in Pequenos Libombos dam, Nhambavale lake, Chòkwé irrigation channels and Chidenguele sites in the South of Mozambique during 2003Mozambique during , 2008Mozambique during , and 2009 and their studies indicated the occurrence of MC-LR, -YR, and -RR produced by Microcystis sp. (M. novacekii, botrys and other) and Cylindrospermopsis raciborskii [117][118][119][120] (Table 4). MC concentration varies from less than 0.01 (below quantification levels) to 0.02 in Pequenos Libombos dam, less to 0.01 to 0.68 in Chòkwé irrigation channels, 0.86 to 7.82 in Nhambavale lake and 0.57 to 6.83 µg•L −1 in Chidenguele.…”
Section: Microcystin In Mozambican Drinking Watermentioning
confidence: 99%
See 2 more Smart Citations